Equality in contention: exploring the debates of gender-equal inheritance rights in Bangladesh - Jinat Hossain; Ishtiaq Jamil (Public Administration and Policy, 2022)
Purpose – The purpose of the paper is to evaluate what caused the debates and confusion in articulating a gender-equal inheritance policy in Bangladesh, and to identify the socio-political drivers and nature of the political power play that thwarted the policy’s adoption. Design/methodology/approach – The research undergirding this paper is based on a qualitative approach involving a case study with in-depth semi-structured interviews, focus-group discussions, and secondary data analysis. The interviews were conducted with policy makers, officials, lawyers, women activists, Muslim religious scholars, Hindu priests, academics and researchers, and women representing Hindu and Muslim religions. Findings – The findings illustrate that the controversies between the Islamic religion and national and international policies led to serious debates and confusion about gender-equal rights of inheritance in Bangladesh. The failure to formulate and adopt a gender-equal inheritance policy was influenced by several socio-political phenomena and gender-biased institutional settings. This kind of policy is deeply political, and cultural compatibility is necessary to formulate it, especially when the policy affects religious sentiments. Religious sentiments and beliefs, which are associated with religion-based personal law, therefore influence both the formulation or non-formulation of a gender-equal policy. To move forward with the fundamental idea of women’s inclusion, there is a strong need to identify the socio-cultural and political drivers behind formulating, non-formulating, as well as implementing a gender-equal policy. Originality/value – The paper will be beneficial to scholars and policy makers who seek to explore the epicenter of challenges and opposition to formulating a gender-equal policy in the context of a developing country with a Muslim majority.